Carbon dioxide (CO2) dry reforming of glycerol for hydrogen production using Ni/La2O3 and Co/La2O3 - Nursofia, Mohd Yunus (2015)
Converting glycerol, obtained from biodiesel industry via dry reforming is considered as a promising route to improve the economic viability of biodiesel industry. The objective of this research work is to synthesize, characterize and conduct the catalytic activity test of CO2 glycerol dry reforming using Nickel (Ni) and Cobalt (Co) supported Lanthanum oxide (La2O3) as catalyst. In this research, Ni/La2O3 and Co/La2O3 were tested in a fixed bed reactor at 700 oC, 1 atm and CO2: glycerol of 1:1. The catalysts were prepared by using wet impregnation method and characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Bruanauer-Emmett-Teller (BET) and Fourier-Transform infrared spectroscopy (FTIR). From the characterization analysis, the results revealed that Ni based supported by La2O3 have smaller metal crystallite size as compared to Co supported La2O3 due to highly-dispersed of La2O3 in the Ni catalyst. The surface morphology of 10 wt% Ni/La2O3 catalyst also shows some crystallite particles with small diameter covered the lanthanum oxides support consistent with XRD result. BET surface area measurement gives higher surface area, 28.29 m2/ g for 10 wt% Ni/La2O3 as compared to 10 wt% Co/La2O3 which gives 13.032 m2/ g. Reaction studies demonstrated that 10 wt% Ni/La2O3 gives the highest performance of hydrogen production and glycerol conversion as compared to calcined La2O3, 5 wt% Ni/La2O3, 15 wt% Ni/La2O3, and 10 wt% Co/La2O3 with the yield and conversion of 11.8 % and 18.6 % respectively. Excellence catalytic performance of 10 wt% Ni/La2O3 may attribute to high activity of 10 wt% Ni/La2O3 towards hydrogen rich gas and great stability. Besides, smaller metal crystallite siz